Pareira, Elisabeth Michaela KAJIAN TERHADAP PERUBAHAN FISIK UMBI KENTANG (Solanum tuberosum L.) SELAMA PENYIMPANAN DI SUHU RUANG: Perubahan Sifat Fisik Kentang selama Penyimpanan - Danella Nabila Balqis Balqis; Elisabeth Michaela Pareira; Nezly Nurlia Putri; Muhamad Rezka Fathan4; Anisa Lismianisarie (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Damage to horticultural commodities after harvest is around 20-40%. This is due to ongoing respiration and metabolism processes, inaccuracy of harvest time, mechanical, physical and physiological damage. Damage to potato tubers that are often encountered in the field is generally caused by the transportation of results and improper post-harvest handling. One of the handling efforts in anticipating damage to potato tubers is using packaging. PP plastic packaging and cardboard are the most popular packaging materials and are very widely used. The purpose of this study was to determine the physical changes of potato tubers during storage at room temperature using PP plastic packaging and cardboard. The method used is descriptive trial and error with the main raw material of local potatoes. Observations were made for 14 days in the form of physical condition of potato tubers in the form of color, shape or texture, measurement of weight and diameter. Observations on the inside of the tuber and dissolved solids were carried out on the 11th day. The results showed that potato tubers stored in PP plastic packaging did not experience many physical changes compared to cardboard packaging. Where potato tubers stored using PP plastic packaging only experienced physical texture softening. Potato tubers stored in cardboard packaging, one of which experienced decay on the 11th day while the other potato tubers were physically still in a fresh condition although the texture was soft on the 14th day. The total value of dissolved solids on day 11 in PP plastic potato tubers was 6% while in cardboard packaging was 5.2%. The longer the storage of potatoes, the more carbohydrates are converted into simple sugars so that the total soluble solids in potato tubers will continue to increase.